Figurative language on visual imagery of Dorothy Parker’s selected poems - Mangkulla, Amalia Irvana; Gustary, Devian Try (Journal of Language and Pragmatics Studies, 2024)
This research aims to analyze the types of figurative language that can be found on visual imagery of selected poems by Dorothy Parker. The data research method used in this research is a qualitative descriptive method. The research problems are, (1) What visual imagery are used in the four selected poems by Dorothy Parker? and (2) What are the types of figurative language that contained on visual imagery of Dorothy Parker’s selected poems? The data sources of this research are four selections of poem by Dorothy Parker, Résumé, Penelope, The Red Dress, and Testament. The result shows there are fifteen visual imagery that used in the four selected poems and contained five types of figurative language, which are personification, metaphor, hyperbole, simile, and irony.